2020
DOI: 10.1007/s00011-020-01358-6
|View full text |Cite
|
Sign up to set email alerts
|

Changes of lipoxin levels during pregnancy and the monthly-cycle, condition the normal course of pregnancy or pathology

Abstract: Objective and Design The purpose of the review was to gather information on the role and possibilities of using lipoxin in the treatment of infertility and maintaining a normal pregnancy. Ovulation, menstruation, embryo implantation, and childbirth are reactions representing short-term inflammatory events involving lipoxin activities. Lipoxin A4 (LXA4) is an arachidonic acid metabolite, and in cooperation with its positional isomer lipoxin B4 (LXB4), it is a major lipoxin in mammals. Biosynthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 105 publications
2
9
0
Order By: Relevance
“…Previous studies have suggested that AA/EPA have positive correlation with inflammatory rate of eicosanoids 47 , 48 , particularly due to AA eicosanoid metabolites 30 , 49 . On the other hand, AA is also found to generate lipoxins, particularly lipoxin (LXA4), which acts as an anti-inflammatory properties that related to obstetrical complications such as preterm and preeclampsia 50 , 51 . Here we showed that the value of ≥ 35 AA/EPA has increased the risk for preeclampsia with sensitivity 83.3% and 84.1%, with significant differences compared to control ( p < 0.001) and high adjusted odds ratio (OR 24.78).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that AA/EPA have positive correlation with inflammatory rate of eicosanoids 47 , 48 , particularly due to AA eicosanoid metabolites 30 , 49 . On the other hand, AA is also found to generate lipoxins, particularly lipoxin (LXA4), which acts as an anti-inflammatory properties that related to obstetrical complications such as preterm and preeclampsia 50 , 51 . Here we showed that the value of ≥ 35 AA/EPA has increased the risk for preeclampsia with sensitivity 83.3% and 84.1%, with significant differences compared to control ( p < 0.001) and high adjusted odds ratio (OR 24.78).…”
Section: Discussionmentioning
confidence: 99%
“…According to its definition, preterm labor refers to pregnancy termination before 37 weeks of gestation. It is one of a common complication in obstetrics [ 1 ]. The incidence of preterm birth exceeds 10% worldwide, affecting more than 15 million births each year [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…A normal menstrual cycle is another important affect factor in fertility intention, which is also consistent with our surveys in China. 35 Reproductive concerns covered fear of infertility, the negative impact of infertility on family relationships, caring for a child in poor health, and concerns about the risks of the child giving birth, which is common among lupus patients. 12 In our study, we have found that reproductive concerns scale was related to fertility intention and included the fertility potential, child's health, personal health, and becoming pregnant which changed fertility intention.…”
Section: Discussionmentioning
confidence: 99%